Critical stab injury due to anatomical variation caused by retroperitoneal lipoblastoma: A case report - Gündüz, Mehmet; Yalçın, Ahmet; Karadeniz, Erdem (Journal of Surgery and Medicine, 2019)
Lipoblastoma and lipoblastomatosis are rare soft tissue neoplasms that are derived from fetal adipose tissue and that are seen in infants and young children. They transform into mature lipomas as the patients age. We present a 23 years old male patient stabbed from left abdominal flank and had a lipoid lesion on the right side of retroperitoneum. Due to malposition of intraabdominal organs in the stabbing site, patient had various vascular and serosal injuries as well as intestinal perforations.